Multidisciplinary team approach in acute myocardial infarction patients undergoing veno-arterial extracorporeal membrane oxygenation - David Hong; Ki Hong Choi; Yang Hyun Cho; Su Hyun Cho; So Jin Park; Darae Kim; Taek Kyu Park; Joo Myung Lee; Young Bin Song; Jin-Oh Choi; Joo-Yong Hahn; Seung-Hyuk Choi; et al. (Annals of Intensive Care, 2020)
Abstract Background Limited data are available on the impact of a specialized extracorporeal membrane oxygenation (ECMO) team on clinical outcomes in patients with acute myocardial infarction (AMI) complicated by cardiogenic shock (CS). This study evaluated whether specialized ECMO team is associated with improved in-hospital mortality in AMI patients undergoing veno-arterial (VA) ECMO. Methods A total of 255 AMI patients who underwent VA-ECMO were included. In January 2014, a multidisciplinary ECMO team was founded at our institution. Eligible patients were classified into a pre-ECMO team group (n = 131) and a post-ECMO team group (n = 124). The primary outcome was in-hospital mortality. Results In-hospital mortality (pre-ECMO team vs. post-ECMO team, 54.2% vs. 33.9%; p = 0.002) and cardiac intensive care unit mortality (pre-ECMO team vs. post-ECMO team, 51.9% vs. 30.6%; p = 0.001) were significantly lower after the implementation of a multidisciplinary ECMO team. On multivariable logistic regression model, implementation of the multidisciplinary ECMO team was associated with reduction of in-hospital mortality [odds ratio: 0.37, 95% confidence interval (CI) 0.20–0.67; p = 0.001]. Incidence of all-cause mortality [58.3% vs. 35.2%; hazard ratio (HR): 0.49, 95% CI 0.34–0.72; p < 0.001) and readmission due to heart failure (28.2% vs. 6.4%; HR: 0.21, 95% CI 0.08–0.58; p = 0.003) at 6 months of follow-up were also significantly lower in the post-ECMO team group than in the pre-ECMO team group. Conclusions Implementation of a multidisciplinary ECMO team was associated with improved clinical outcomes in AMI patients complicated by CS. Our data support that a specialized ECMO team is indispensable for improving outcomes in patients with AMI complicated by CS.